A study of knowledge, attitude and perception of perimenopausal changes in women aged 40-45 years in Gurugram district of Haryana, India - Nath, Jayati; Raval, Atri; Ghanshyam Jain, Nikita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Menopause, defined as cessation of menstruation for at least one year duration, due to exhaustion of the ovarian functions. ’Perimenopause’ or ’climacteric’ is the period of transition in which the woman’s body makes the changes for menopause. Methods: A cross- sectional study by recruiting 100 female participants between 40-45 years. Results: 56% women have not heard about the term menopause or perimenopause. 50% thought that stoppage of menstrual cycle was a natural phenomenon and 70% had no idea about the risk factors of perimenopause or menopause. 68% females did not know about hormone replacement therapy. Conclusions: More spread of awareness and health education is needed regarding the same so as to clarify the doubts and bust the many myths existing so as to help women have a smooth transition to menopause and have a healthy and productive post-menopausal life.